Key performance indicators in freestyle swimming: Comparing start, turn, and swimming velocity in top-elite female junior and adult swimmers - Widmer, C.; Hernandez, J.; Romann, M.; Taube, W.; Born, D.-P. (Current Issues in Sport Science, 2025)
Introduction Due to the increasing importance of start and turn performance in swim races throughout the recent years, the aim of the study was to compare the effect of start performance, turn performance, and swimming velocity on the race result between top-elite female junior and adult swimmers across all distances of freestyle pool races (50 m to 1500 m) and to provide a software tool to predict race outcomes based on the various key performance indicators.